Basic statistics for psychologists - Brysbaert, Marc. (Houndsmill, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
"Basic Statistics for Psychologists combines clear explanations of statistical concepts and tests with a guide to using SPSS, providing an invaluable resource for psychology students. Highly readable and with innovative learning features throughout, this book offers a comprehensive introduction to statistics and their use in social science"--Provided by publisher.
Using statistics in psychology research -- Summarising data using the frequency distribution -- Summarising data using measures of central tendency -- Summarising data using measures of variability -- Standardised scores, normal distribution, and probability -- Using the t-test to measure the difference between independent groups -- Interpreting the results of a statistical test -- Non-parametric tests of difference between independent groups -- Using the t-test to measure change in related samples -- Non-parametric tests to measure changes in related samples -- Improving predictions through the Pearson correlation coefficient -- Improving predictions through non-parametric tests -- Using analysis of variance for multiple independent variables -- Going further : more than two levels and multiple predictors.
Includes index.
Keywords: Psychology; Psychometrics